STUDI PEMANFAATAN BOTTOM ASH UNTUK PENCEGAHAN AIR ASAM TAMBANG DAN MENURUNKAN KONSENTRASI LOGAM TERLARUT PADA BATUAN BREKSI VULKANIK DENGAN SKALA LABORATORIUM - Setia Budi, Agung; Marpaung, Nalom D; Onwardana, M. Eka (LPPM ISTP, 2023)
Mining activities have the potential for contamination in the form of acid mine drainage. Prevention of acid mine drainage (AAT) can be carried out by covering materials that have the potential to form AAT (Potentially Acid Forming / PAF) using non-potential (Non Acid Forming / NAF) materials. So that it can stop or reduce the contact between sulfide minerals with air and / or water. However, the presence of NAF material is often not found in large quantities to be able to isolate all PAF materials. Therefore, another material is needed as an alternative in preventing AAT formation. One of the materials that has the potential to be used is bottom ash which is the result of burning coal at the PLTU. A study was conducted with samples of volcanic breccias which are PAF rocks and volcanic breccias mixed with bottom ash material using the Leach Column Test (LCT) method. LCT test results obtained varying pH values and dissolved metal ions. In volcanic breccias, the pH value fluctuates in the range of 2.3-0.8 with high dissolved metals. Meanwhile, volcanic breccias mixed with bottom ash obtained pH values that were retained between 3.57-3.56 with low dissolved metal concentrations. The test results show that the addition of 30% bottom ash can increase the pH value and decrease the dissolved metal concentration in volcanic breccia. The addition of bottom ash material can increase the pH of volcanic breccias but is not able to neutralize the acidity of volcanic breccias.